An analysis of Anzara Bangladesh Limited's influencer marketing campaigns and their impact on customer engagement - Onty, Meharin Islam (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.